Analisis Butir Soal Matematika UN SMP/MTs Tahun 2018/2019 Ditinjau dari Kriteria Koneksi Matematis - Hasbullah, Habib (Efektor, 2020)
Mathematical connection ability is one of the abilities students must have in learning mathematics. The importance of mathematical connection ability is inseparable from the characteristics of mathematics which is a hierarchically structured science and interrelated between one concept with another concept. In addition to the relationship between concepts in mathematics, aspects of mathematical connections also contain connections between mathematical concepts and other fields of science and the relationship between mathematics and everyday life. Considering the importance of the ability of these mathematical connections, mathematical connection questions are also included in the National Mathematics Examination at various levels. This study examines the components of the Mathematics National Examination items that meet the mathematical connection criteria. The objectives of this study are: a) to find out the percentage of School Exam questions that meet the mathematical connection criteria, b) find out examples of School Exam questions that meet the mathematical connection criteria. The results of this study indicate that 80% of school exam questions meet the mathematical connection criteria.